Comparison of tool wear during friction stir welding of Al alloy and Al-SiC metal matrix composite. (October 2021) - Bist, Ashish; Saini, JS; Sharma, Vikas
Aluminum matrix composites have received considerable attention due to their high specific strength and specific stiffness, high hardness, and wear resistance along with being light in weight. These composites are preferably joined using friction stir welding process. The major concern in friction stir welding is the wear of the welding tool pin which is the backbone of the process. The wear is due to the prolonged contact between the tool and the harder reinforcements in the composite materials. The present work deals with the study of tool wear and its surface roughness with respect to different selected friction stir welding parameters such as rotational speed, transverse speed, length of weld, and different composition of Aluminum composite. It was found that the total amount of material removed from the tool and the surface roughness of the tool is in direct proportion to the rotational speed of the tool and the length of the weld but inversely proportional to the transverse rate. The increase in wt.% of SiC reinforcement leads to the higher tool wear but reduces the surface roughness of the tool.